Passive microwave remote sensing of the Earth's surface - Ulaby, F. (IEEE transactions on antennas and propagation, 1976)
This is a brief review paper on microwave radiometry as a remote sensing tool in geoscientific investigations. Topics covered include basic radiometric principles, radiometer receivers, and applications. This paper is one in a series of mini-reviews sponsored by the Wave Propagation Standards Committee of IEEE and is intended primarily for those persons who have not had occasion to study extensively in the subject.